Distinctive morphological variation of saccular otoliths in relation to hermaphroditism type in Sarpa salpa and Serranus scriba (Teleostei: Perciformes) from the Mediterranean Sea in Bizerte, Tunisia - Bakkari Wided; Mejri Marwa; Bouriga Nawzet; Mili Sami; Chalh Abdellah; Shahin Adel AB; Quignard Jean-Pierre; Trabelsi Monia; Faleh Abderraouf Ben (Oceanological and Hydrobiological Studies)
This study aimed to describe and compare the morphological characteristics of saccular otoliths (sagittae) in the protandrous hermaphrodite Sarpa salpa and the synchronous hermaphrodite Serranus scriba collected from the Bizerte site located in northwestern Tunisia, and to examine the effect of hermaphroditism type on the otolith shape and size at the inter- and intraspecific levels, using elliptical Fourier analysis. At the interspecific level, a significant bilateral asymmetry in shape was observed between the left and right otoliths. At the intraspecific level, a significant bilateral asymmetry in shape was detected between the left and right otoliths only in S. scriba. Discriminant function analysis (DFA) produced two separate main groups corresponding to the two species, and intrasexually differentiated between left and right otoliths in S. salpa. In addition, a significant bilateral asymmetry was found in Lo, Wo, Ao, and Po in S. salpa and in Po only in synchronous S. scriba. Thus, protandrous hermaphroditism did not affect otolith shape in S. salpa, but showed an apparent bilateral asymmetry in otolith size. However, synchronous hermaphroditism exhibited a significant bilateral asymmetry in otolith shape and Po only in S. scriba. The causes of this significant inter- and intraspecific bilateral asymmetry observed in otolith shape and size were discussed.